Cambodia : 2007 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation underlies that strong macroeconomic policies have enabled Cambodia to achieve impressive growth and make inroads into poverty. Supported by prudent fiscal and monetary policies that have strengthened the economy's resilience to shocks, growth has averaged more than 9 percent since 2000, accelerating in recent years. Progress has been made on structural reforms but much remains to be done. Efforts in the fiscal and financial sectors are bearing fruit, with notable achievements being the implementation of new government expenditure and accounting procedures and strengthened prudential regulations for the banking sector.